Variant analysis of the efficiency of industrial scale power station based on DC-SOFCs and DC-MCFCs. (1st August 2018) - Kupecki, Jakub; Skrzypkiewicz, Marek; Motylinski, Konrad
Abstract: The concept of direct carbon fuel cell (DCFC) can be realized using different types of fuel cells. The most important advances were achieved for solid oxide fuel cells or molten carbonate fuel cells, DC-SOFC and DC-MCFC, respectively. Utilization of solid fuels, such as coal, char or biochar in high temperature electrochemical reaction offers a great potential in terms of the electric efficiency. While in conventional gas-fed fuel cells the transference number is equal 2, the electrochemical oxidation of solid fuel - in theory - can be realized with ion transfer number of 4. In the current study several configurations of DCFC systems based on SOFCs and MCFCs were analysed. The focus was on determining the efficiency for systems with different methods of delivering the fuel and alternative post-combustion systems. The article presents variant analysis of eight configurations of power plants based on DCFCs. The modified parameters included the cell voltage, effective transference number and the fuel utilization. Each configuration is presented and discussed. The efficiency of the alternative configurations lays in the range from 36 to 64% (LHV-based). Authors explain the methodology of the study and quantify the results as well provide justification concerning the Assumptions. Graphical abstract: Image Highlights: Several alternative configurations of DCFC-based systems were analysed. The solid oxide fuel cells and molten carbonate fuel cells were considered. Energy efficiency was performed with conservative Assumptions. Assumptions were supported by experimental studies. Efficiency of the systems lays in the range from 36 to 64% (LHV-based).